2000
DOI: 10.1109/23.903776
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of accelerated total dose testing of linear bipolar circuits

Abstract: Different part types of linear bipolar technology were irradiated in order to evaluate the ability of accelerated total dose testing to describe the tolerance at very low dose rate. On all tested types, the bias current was the most sensitive parameter. Results confirm that elevated temperature irradiation performed at high dose rate is well adapted to define the tolerance of the bias current at very low dose rate. The best accelerated test conditions correspond to a dose rate of 0.55 rad/s and irradiation tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 12 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…For many ICs, it has been shown that the input current in the input transistors is a good indicator of current gain degradation, at least for moderate total dose levels [11], before the device degradation saturates [12]. In this work, the investigated critical parameter is thus the input current [13], [14]. The excess current, called excess here, was normalized to its pre-irradiation value according to the following equation: (1) where and are the base current value before and after irradiation, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…For many ICs, it has been shown that the input current in the input transistors is a good indicator of current gain degradation, at least for moderate total dose levels [11], before the device degradation saturates [12]. In this work, the investigated critical parameter is thus the input current [13], [14]. The excess current, called excess here, was normalized to its pre-irradiation value according to the following equation: (1) where and are the base current value before and after irradiation, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…For example, it will take about 4 months to accumulate 100 krad(Si) when performing at typical LDR (0.01 rad(Si)/s) experiment. So, several accelerated test techniques have been attempted to evaluate ELDRS, such as (i) elevated temperature irradiation (ETI), [3,10] (ii) irradiation with molecular hydrogen, [6,11] (iii) the switched dose rate technique, [12,13] and (iv) the switched temperature irradiation. [14][15][16] Among them, switched temperature technique, proposed by Lu et al [14] as a promising and applicable accelerated ELDRS test method, has been demonstrated on a series of bipolar devices by experimental verification.…”
Section: Introductionmentioning
confidence: 99%
“…Accelerated total dose testing, i.e., experiments done at high dose rate and high temperature are shown to closely determine tolerance at very low dose rate and at room temperature (RT) [12]. Also, this is shown to be more valid for determining bias parameter degradation than offset parameters at low dose rate, at RT.…”
Section: Literature Reviewmentioning
confidence: 99%